Outpatient intravenous diuresis in a rural setting: safety, efficacy, and outcomes - Pathangey, Girish; D’Anna, Susan P; Moudgal, Rohitha A.; Min, David B.; Manning, Katharine A.; Taub, Cynthia C.; Gilstrap, Lauren G. (Frontiers in Cardiovascular Medicine, 2023)
Purpose To evaluate the safety, efficacy, and outcomes of outpatient intravenous diuresis in a rural setting and compare it to urban outcomes. Methods A single-center study was conducted on 60 patients (131 visits) at the Dartmouth-Hitchcock Medical Center (DHMC) from 1/2021-12/2022. Demographics, visit data, and outcomes were collected and compared to urban outpatient IV centers, and inpatient HF hospitalizations from DHMC FY21 and national means. Descriptive statistics, T-tests and chi-squares were used. Results The mean age was 70±13 years, 58% were male, and 83% were NYHA III-IV. Post-diuresis, 5% had mild-moderate hypokalemia, 16% had mild worsening of renal function, and 3% had severe worsening of renal function. No hospitalizations occurred due to adverse events. The mean infusion-visit urine output was 761±521ml, and post-visit weight loss was -3.9±5.0kg. No significant differences were observed between HFpEF and HFrEF groups. 30-day readmissions were similar to urban outpatient IV centers, DHMC FY21, and the national mean (23.3% vs. 23.5% vs. 22.2% vs. 22.6%, respectively; p=0.949). 30-day mortality was similar to urban outpatient IV centers but lower than DHMC FY21 and the national means (1.7% vs. 2.5% vs. 12.3% vs. 10.7%, respectively; p<0.001). At 60 days, 42% of patients had ≥1 clinic revisit, 41% had ≥1 infusion revisit, 33% were readmitted to the hospital, and one death occurred. The clinic avoided 21 hospitalizations, resulting in estimated cost savings of 426,111. Conclusion OP IV diuresis appears safe and effective for rural HF patients, potentially decreasing mortality rates and healthcare expenses while mitigating rural-urban disparities.